When the Synchrotron radiations highlight the Randall's plaques and kidney concretions - Daudon, M; Bazin, D (Journal of physics. Conference series, 2013)
In western countries, a dramatic increase in papilla calcifications (Randall's Plaque or RP) is observed as a major cause of calcium oxalate kidney stones. Through ex vivo X-ray absorption spectroscopy, we give for the first time direct structural evidence of the presence of amorphous carbonated calcium phosphate in these Randall's plaques (RP). Such chemical composition of RP present in increasingly young subjects raises a major question regarding alimentation: does nutrient-enriched food especially aimed at young children affect the physiology of the kidney? Moreover, lithogenic diseases may induce intratubular crystallization and end-stage renal failure. We show that Fourier transform infrared microspectroscopy is able to characterize such pathological microcalcifications giving their chemical composition and their spatial distribution, thus providing invaluable information for the diagnosis of the disease and the treatment of the patients.